Monitoring the Spectral Back Scattering of Lodged Dry-direct Seeded Rice by Temporal Sentinel - I Data - Reddy, M. Bhargav; Neelima, T. L.; Srikanth,; Devi, M. Uma (International Journal of Bio-resource and Stress Management, 2025)
The study was conducted from June, 2020 to January, 2021 in two villages namely; Chinna Tandrapadu and Mandoddi of Ieeja Mandal, Gadwal district, Telangana, India to assess the lodged crop using the sentinel-I data with two polarizations and two cross polarisations backscatter values. The two major methods were direct Seeding and transplanting. In direct-seeded rice, seeds were directly sown in the field, the plants did not have deep root penetration and were susceptible to crop lodging, a major problem during the flowering and grain-filling stages, leading to crop loss and damage during the monsoon season. The area under the crop was estimated using remote sensing, which provided real-time, reliable, and quick information. Microwave data with its longer wavelength (1 mm to 100 mm) could penetrate through clouds and other atmospheric particles, and hence its usage in monitoring rice ecosystems gained importance. In this study, Sentinel-1A images were utilized for analysis. The multi-temporal C-band dual-polarization VV, VH, and their combinations VV VH-1 and VH VV-1 backscattering values were studied throughout the crop growth period. The backscatter values obtained from the crop during the growth stages were analyzed using the paired t-test. It revealed that the flowering, dough, and maturity stages were the periods when the lodged crop could be discriminated from the unlodged crop at the VV and VH polarizations. The band cross-combinations VV VH-1 and VH VV-1 were not able to discriminate the lodged crop.